Knowledge, attitudes and practices of pregnant women in Martinique in the immediate aftermath of the Zika virus outbreak. (March 2018) - Delet, J.; Cabié, A.; Merle, S.; Voluménie, J.-L.; Monthieux, A.
Abstract: Introduction: The WHO and the HCSP recognize the Zika virus as a public health problem of international concern primarily because of the foetal risks. During the epidemic in Martinique, several modifications to the normal obstetrical follow-up were set up and information had to be delivered to pregnant women about these modifications, the attitudes to prevent infection and the signs motivating additional visits. The objective of our work was to evaluate the knowledge, attitudes and practices of pregnant women in Martinique about the risks associated with Zika infection during pregnancy in the immediate aftermath of the epidemic. Materials and methods: A descriptive cross-sectional survey was conducted from February to May 2017. It took place through an anonymous and standardized face-to-face questionnaire. The questions dealt with the pregnant women general knowledge about the virus, information disseminated by media on this subject, the potential risks, the protective measures taken and the monitoring throughout the pregnancy in case of infection. Results: The total sample consisted of 297 pregnant women. Despite a weak adherence to individual and domestic protection recommendations, we found a good level of knowledge about Zika virus from pregnant women in Martinique. The fetal risk in case of maternal infection was known for 96.6% of those surveyed, individual protective measures were followed by 64.6% of women, 77.0% knew where to go in case of suspected infection, and 79.4% reported that the modifications in follow-up mainly concerned ultrasound monitoring. Conclusion: The awareness campaign on zika virus had a significant impact on population's knowledge and main practical information was correctly captured. The information did not spill excessive fear. Nevertheless, modification of individual behavior appeared harder to obtain.